Knowledge, Attitude and Practices of Musculoskeletal Disorder Injuries from Malaysian Industries Employers’ Perspective - Nadia Nordin, Athirah; Mohd. Rohani, Jafri; Zainal Abidin, Noesheila; Md. Zein, Raemy; Amira Mat Zuki, Anis (International Journal of Engineering and Technology, 2018)
This study aims to assess the level of Knowledge, Attitude and Practices (KAP) on Musculoskeletal disorders (MSDs) from employers’ perspectives in Malaysia industries. A newly developed KAP questionnaire was distributed and answered by 45 employers. Most employers showed good scores in the majority of items in Knowledge, Attitude and Practices sections. Pearson correlation was used in order to test the relationship between KAP scores and demographic profile and also KAP variables. It was found that knowledge has strong correlation r=0.291, p>0.05 with gender. The attitude component has a strong correlation (r=0.344, p>0.05) with age group. Whereas the practices component has good correlation with education level (r=0.249, p>0.05). However, the KAP variables show only knowledge and practices have a strong correlation (r=0.271, p>0.05). MSDs cases are increasing hence understanding the underlying KAP factors are crucial in order to tackle the problem.
Keywords: Employer; KAP; Musculoskeletal disorders; Perspective.